ZECOM Engineering Berhad Excellence Award 2002 - Universiti Malaysia Sarawak, Faculty of Engineering (Universiti Malaysia Sarawak (UNIMAS), 2002)
ZECON Engineering Berhad excellence award 2002 has been held at Main Meeting Room at Chancellor Building at been officially launched by LPU UNIMAS Chairperson YBhg Datuk Hatta Solhi and Vice Canselor of UNIMAS YBhg Prof. Datuk Dr. Yusuf Hadi.